2015
DOI: 10.1002/lsm.22410
|View full text |Cite
|
Sign up to set email alerts
|

Acne scarring: A review of available therapeutic lasers

Abstract: We sought to provide a framework for understanding the various types of lasers available to treat acne scars and review the primary literature pertaining to the efficacy, safety, and advantages of each laser discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0
6

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 74 publications
(257 reference statements)
0
56
0
6
Order By: Relevance
“…Although a significant difference was not found between the two groups, the subjective scale was slightly higher in group F than in group D. The efficacy of nonablative 1550-nm fractional laser was reported for the treatment of acne scarring. 16,17 In one case series, two patients with acne improved in erythema after 5-6 months of the laser treatment. 18 Therefore, the difference in patients' subjective scales observed between the groups could be due to these additional effects of nonablative fractional laser.…”
Section: Discussionmentioning
confidence: 99%
“…Although a significant difference was not found between the two groups, the subjective scale was slightly higher in group F than in group D. The efficacy of nonablative 1550-nm fractional laser was reported for the treatment of acne scarring. 16,17 In one case series, two patients with acne improved in erythema after 5-6 months of the laser treatment. 18 Therefore, the difference in patients' subjective scales observed between the groups could be due to these additional effects of nonablative fractional laser.…”
Section: Discussionmentioning
confidence: 99%
“…However, the safety and efficacy profiles of all these therapies is often considered as problematic, and several studies demonstrated that these treatments are not capable of affecting all etiological factors involved in acne pathogenesis . Therefore, there is an urgent need to further develop alternative and innovative treatments, such as light, laser, and photodynamic therapies (PDT) . Light and laser therapy for the treatment of acne vulgaris is based on the observation that P. acnes synthesizes chromophores such as porphyrins, more specifically, coproporphyrin .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Therefore, there is an urgent need to further develop alternative and innovative treatments, such as light, laser, and photodynamic therapies (PDT). [6][7][8][9] Light and laser therapy for the treatment of acne vulgaris is based on the observation that P. acnes synthesizes chromophores such as porphyrins, more specifically, coproporphyrin. [10][11][12] Porphyrins enable light therapy to exert a selective cytotoxic effect on P. acnes.…”
Section: Introductionmentioning
confidence: 99%
“…Various therapeutic lasers are available for acne scar . Laser procedures for acne can cause persistent erythema or pigmentary changes and may lead to legal disputes .…”
Section: Discussionmentioning
confidence: 99%